THE INFLUENCE OF TEACHER PROFESSIONAL EDUCATION (PPG) ON THE PERFORMANCE OF PAI TEACHERS IN IMPROVING LEARNING METHODS AT SDN 1 PATALAN BANTUL - Laode, Moh Tri Kurniawan; Edi Suherman; Muhammad Hidayatu Rohman; Agustin Anggraini; Gesita Zahra Tirtia Pradana (Indonesian Journal of Islamic and Social Science, 2024)
The quality of a country's education is determined by the quality of its educators. Teachers who provide primary, secondary and early childhood education must have competencies and qualifications that are in accordance with national education standards. The Pre-Service Teacher Professional Education Program is an innovative program to prepare prospective certified teachers at SDN 1 Patalan Bantul. Educational requirements for teachers include a minimum of a bachelor's degree and must have educator certification obtained through an accredited program. After being certified by the Teacher Professional Education and Training Program, the entire certification process is carried out by Teacher Professional Education. This research uses a qualitative approach using library research methods to investigate how teacher training policies in Indonesia meet the needs of professional teachers